Child marriage and domestic violence - Pratibha Sharma (Jaipur Mark Publishers, 2023)
Honour killing; dowry deaths; effects of domestic violence on children; psychological and economic abuse; parental bullying of children; violence against women; forced marriage and child marriage; epidemiology of domestic violence; management of domestic violence.
Keywords: Social Problems & Services